10 years later: Did the Arab Spring fail? - Aarts, Paul (Malala, 2021)
The self-immolation of the Tunisian street vendor Mohammed Bouazizi on the 17th of December 2010 led to a wave of protests in the Arab world. Now, gloom reigns allover. (Civil) wars, repression and growing unemployment plague the region like never before. The ‘double crisis’ of the collapsed oil market and COVID-19 further deepened existing problems. Was the Arab Spring doomed to fail? Which lens should we look through to understand the potential of the waves of protests?